Da’i Technology Literacy in Perspective of the Qur'an - Cecep Castrawijaya (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2023)
The dai's technological literacy is the ability to use, understand, manage and assess an innovation that involves a scientific process to solve problems and know the dai's abilities related to literacy problems. This research aims to reveal the concept of dai's technological literacy in the view of the Koran and to find out the dai's technological literacy competence. The method used in this research is the descriptive analysis method, while the approach method used in this research is a qualitative approach through literature study. The results of this study indicate that the concept of information literacy in the Koran leads to the implementation of information retrieval. In contrast, the concept of communication literacy in the view of the Koran refers to morals and ethics in communication. In addition, technological literacy competencies include basic, primary, intermediate, advanced, technical, and literacy skills. This research implies that the preachers are expected to be able to upgrade themselves and have established literacy in the field of technology so that they can maintain their da'wah activities according to the times.